Sheep Bone Powder (SBP) as a Partial Cement Replacement in Concrete - Lile, Nuradila; Mokhtar, Norfaniza (Recent Trends in Civil Engineering and Built Environment, 2025)
Animal bone take a longer time to be disposed compared to other domestic waste. The indiscriminate of the animal bone in the environment has led the search for the solution by recycling the bone to form a new product in the construction industry such as a partial cement replacement in concrete. Hence, the cement was replaced by weight in mix proportion (2%, 4%, 6%, 8%, 10% and 12%). The propose of the study is to determine the optimum percentage of Sheep Bone Powder as a partial cement replacement in the concrete and understand its effect on the concrete’s microstructure. To ensure that the objective will be achieve, a combination of deep literature study and data gathered from the laboratory testing is necessary. The literature review provides an insight about the previous study to support the data collection. The data was obtained from the compressive strength test and SEM-EDX analysis on sample sized for C30 grade concrete. The mix proportion used is 1:1.8:3.2 with 0.5 of water cement ratio. The cube sample with dimension of 100mm x 100mm x 100mm were used and tested after cured in water for 7 days and 28 days. The study concludes that 8% SBP is the optimum proportion, exhibiting the highest compressive strength which is 35MPa and shows a favourable microstructure. Furthermore, the result shows that if the SBP powder increase, the workability of concrete also increased. Following the findings, a several recommendations being proposed to improve the concrete performance. These suggestions have a potential to improve the concrete properties and can help to minimize the environment impact.